2010
DOI: 10.1002/art.27218
|View full text |Cite
|
Sign up to set email alerts
|

Mortality outcomes in pediatric rheumatology in the US

Abstract: Objective. To describe mortality rates, causes of death, and potential mortality risk factors in pediatric rheumatic diseases in the US.Methods. We used the Indianapolis Pediatric Rheumatology Disease Registry, which includes 49,023 patients from 62 centers who were newly diagnosed between 1992 and 2001. Identifiers were matched with the Social Security Death Index censored for March 2005. Deaths were confirmed by death certificates, referring physicians, and medical records. Causes of death were derived by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 38 publications
5
47
0
7
Order By: Relevance
“…Seven cases of the macrophage activation syndrome were reported in these trials, with two associated deaths. 38,39 The mortality rate in phase 2 18 and phase 3 trials of canakinumab (2% over an average of 547 days) is in line with the mortality rate associated with systemic JIA, as reported by Hashkes et al 40 A limitation of the two studies is that patients without fever were excluded from participation. Indeed, in a subset of patients with systemic JIA, systemic symptoms eventually resolve while chronic arthritis continues.…”
Section: Discussionsupporting
confidence: 53%
“…Seven cases of the macrophage activation syndrome were reported in these trials, with two associated deaths. 38,39 The mortality rate in phase 2 18 and phase 3 trials of canakinumab (2% over an average of 547 days) is in line with the mortality rate associated with systemic JIA, as reported by Hashkes et al 40 A limitation of the two studies is that patients without fever were excluded from participation. Indeed, in a subset of patients with systemic JIA, systemic symptoms eventually resolve while chronic arthritis continues.…”
Section: Discussionsupporting
confidence: 53%
“…Studies conducted in Cleveland also revealed a persistent significant mortality among jSLE patients in comparison to that observed over the previous years [14]. In this study, the analysis also demonstrated a changed incidence of various clinical and immunological manifestations.…”
Section: Discussionsupporting
confidence: 66%
“…Laboratory abnormalities include decrease in white blood cells, platelet and haemoglobin, hypertransaminasemia, hyperferritinemia and evidence of intravascular coagulation 1. MAS causes significant morbidity and mortality accounting for a significant portion of the deaths due to sJIA 2 3…”
Section: Introductionmentioning
confidence: 99%